Effect of DNA Origami Nanostructures on Bacterial Growth - Garcia-Diosa, Jaime Andres; Grundmeier, Guido; Keller, Adrian (ChemBioChem)
DNA origami nanostructures are a powerful tool in biomedicine and can be used to combat drug‐resistant bacterial infections. However, the effect of unmodified DNA origami nanostructures on bacteria is yet to be elucidated. With the aim to obtain a better understanding of this phenomenon, the effect of three DNA origami shapes, i.e., DNA origami triangles, six‐helix bundles (6HBs), and 24‐helix bundles (24HBs), on the growth of Gram‐negative Escherichia coli and Gram‐positive Bacillus subtilis is investigated. These results reveal that while triangles and 24HBs can be used as a source of nutrients by E. coli and thereby promote population growth, their effect is much smaller than that of genomic single‐ and double‐stranded DNA. However, no effect on E. coli population growth is observed for the 6HBs. On the other hand, B. subtilis does not show any significant changes in population growth when cultured with the different DNA origami shapes or genomic DNA. The detailed effect of DNA origami nanostructures on bacterial growth thus depends on the competence signals and uptake mechanism of each bacterial species, as well as the DNA origami shape. This should be considered in the development of antimicrobial DNA origami nanostructures.
Keywords: Organic Chemistry; Molecular Biology; Molecular Medicine; Biochemistry

A Comparative Kinetic and Computational Investigation of the Carbon‐Sulfur Cross Coupling of Potassium Thioacetate and 2‐Bromo Thiophene Using Palladium/Bisphosphine Complexes - Peschtrich, Sebastian; Schoch, Roland; Kuckling, Dirk; Paradies, Jan (European Journal of Organic Chemistry)
Abstract We conducted an investigation into the palladium‐catalyzed carbon‐sulfur cross‐coupling reaction involving a 2‐bromothiophene derivative and potassium thioacetate as a substitute for hydrogen sulfide. This investigation utilized kinetic and computational methods. We synthesized two palladium complexes supported by the bisphosphane ligands bis(diphenylphosphino)ferrocene (DPPF) and bis(diisopropylphosphino)ferrocene (D i PPF), as well as their tentative intermediates in the catalytic cycle. Reaction rates were measured and then compared to computational predictions.
Keywords: Organic Chemistry; Physical and Theoretical Chemistry

Pillar[5]arene-based dually crosslinked supramolecular gel as a sensor for the detection of adiponitrile - Rodin, Maksim; Helle, David; Kuckling, Dirk (Polymer Chemistry)
An SPR-based dually crosslinked gel sensor for adiponitrile bearing pillar[5]arene responsive sites with a low limit of detection was developed.
Keywords: Organic Chemistry; Polymers and Plastics; Biochemistry; Bioengineering

Dynamics of DNA Origami Lattices - Julin, Sofia; Keller, Adrian; Linko, Veikko (Bioconjugate Chemistry)
Keywords: Organic Chemistry; Pharmaceutical Science; Pharmacology; Biomedical Engineering; Bioengineering; Biotechnology

Frustrated Lewis Pair Catalysed Reactions - Zhou, Rundong; Tavandashti, Zoleykha; Paradies, Jan (SynOpen)
In recent years, frustrated Lewis pairs have been widely used in small molecules activation and catalytic transformations. This graphic review is aimed to provide the fundamental understanding of frustrated Lewis pair reactivity and the exploitation thereof in catalytic reactions.
Keywords: Organic Chemistry; Materials Science (miscellaneous); Biomaterials; Catalysis

Developing Quantitative Nondestructive Characterization of Nanomaterials: A Case Study on Sequential Infiltration Synthesis of Block Copolymers - Cara, Eleonora; Hönicke, Philipp; Kayser, Yves; Lindner, Jörg K. N.; Castellino, Micaela; Murataj, Irdi; Porro, Samuele; Angelini, Angelo; De Leo, Natascia; Pirri, Candido Fabrizio; Beckhoff, Burkhard; Boarino, Luca; et al. (ACS Applied Polymer Materials)
Keywords: Organic Chemistry; Polymers and Plastics; Process Chemistry and Technology

Effect of Ionic Strength on the Thermal Stability of DNA Origami Nanostructures - Hanke, Marcel; Tomm, Emilia; Grundmeier, Guido; Keller, Adrian (ChemBioChem)
Keywords: Organic Chemistry; Molecular Biology; Molecular Medicine; Biochemistry

Diquat Based Dyes: A New Class of Photoredox Catalysts and Their Use in Aerobic Thiocyanation - Meier, Armin; Badalov, Sabuhi; Biktagirov, Timur; Schmidt, Wolf Gero; Wilhelm, René (Chemistry – A European Journal)
A series of new organic donor–π–acceptor dyes incorporating a diquat moiety as a novel electron-acceptor unit have been synthesized and characterized. The analytical data were supported by DFT calculations. These dyes were explored in the aerobic thiocyanation of indoles and pyrroles. Here they showed a high photocatalytic activity under visible light, giving isolated yields of up to 97 %. In addition, the photocatalytic activity of standalone diquat and methyl viologen through formation of an electron donor acceptor complex is presented.
Keywords: General Chemistry; Catalysis; Organic Chemistry

Electrode Potential-Dependent Studies of Protein Adsorption on Ti6Al4V Alloy - Duderija, Belma; González-Orive, Alejandro; Ebbert, Christoph; Neßlinger, Vanessa; Keller, Adrian; Grundmeier, Guido (Molecules)
This article presents the potential-dependent adsorption of two proteins, bovine serum albumin (BSA) and lysozyme (LYZ), on Ti6Al4V alloy at pH 7.4 and 37 °C. The adsorption process was studied on an electropolished alloy under cathodic and anodic overpotentials, compared to the open circuit potential (OCP). To analyze the adsorption process, various complementary interface analytical techniques were employed, including PM-IRRAS (polarization-modulation infrared reflection-absorption spectroscopy), AFM (atomic force microscopy), XPS (X-ray photoelectron spectroscopy), and E-QCM (electrochemical quartz crystal microbalance) measurements. The polarization experiments were conducted within a potential range where charging of the electric double layer dominates, and Faradaic currents can be disregarded. The findings highlight the significant influence of the interfacial charge distribution on the adsorption of BSA and LYZ onto the alloy surface. Furthermore, electrochemical analysis of the protein layers formed under applied overpotentials demonstrated improved corrosion protection properties. These studies provide valuable insights into protein adsorption on titanium alloys under physiological conditions, characterized by varying potentials of the passive alloy.
Keywords: Chemistry (miscellaneous); Analytical Chemistry; Organic Chemistry; Physical and Theoretical Chemistry; Molecular Medicine; Drug Discovery; Pharmaceutical Science

Multiprotein Adsorption from Human Serum at Gold and Oxidized Iron Surfaces Studied by Atomic Force Microscopy and Polarization-Modulation Infrared Reflection Absorption Spectroscopy - Huang, Jingyuan; Qiu, Yunshu; Lücke, Felix; Su, Jiangling; Grundmeier, Guido; Keller, Adrian (Molecules)
Multiprotein adsorption from complex body fluids represents a highly important and complicated phenomenon in medicine. In this work, multiprotein adsorption from diluted human serum at gold and oxidized iron surfaces is investigated at different serum concentrations and pH values. Adsorption-induced changes in surface topography and the total amount of adsorbed proteins are quantified by atomic force microscopy (AFM) and polarization-modulation infrared reflection absorption spectroscopy (PM-IRRAS), respectively. For both surfaces, stronger protein adsorption is observed at pH 6 compared to pH 7 and pH 8. PM-IRRAS furthermore provides some qualitative insights into the pH-dependent alterations in the composition of the adsorbed multiprotein films. Changes in the amide II/amide I band area ratio and in particular side-chain IR absorption suggest that the increased adsorption at pH 6 is accompanied by a change in protein film composition. Presumably, this is mostly driven by the adsorption of human serum albumin, which at pH 6 adsorbs more readily and thereby replaces other proteins with lower surface affinities in the resulting multiprotein film.
Keywords: Chemistry (miscellaneous); Analytical Chemistry; Organic Chemistry; Physical and Theoretical Chemistry; Molecular Medicine; Drug Discovery; Pharmaceutical Science